A Nonsense Variant in the ACADVL Gene in German Hunting Terriers with Exercise Induced Metabolic Myopathy. Issue 5 (1st May 2018) - Lepori, Vincent; Mühlhause, Franziska; Sewell, Adrian C; Jagannathan, Vidhya; Janzen, Nils; Rosati, Marco; Alves de Sousa, Filipe Miguel Maximiano; Tschopp, Aurélie; Schüpbach, Gertraud; Matiasek, Kaspar; Tipold, Andrea; Leeb, Tosso; et al.
Abstract: Several enzymes are involved in fatty acid oxidation, which is a key process in mitochondrial energy production. Inherited defects affecting any step of fatty acid oxidation can result in clinical disease. We present here an extended family of German Hunting Terriers with 10 dogs affected by clinical signs of exercise induced weakness, muscle pain, and suspected rhabdomyolysis. The combination of clinical signs, muscle histopathology and acylcarnitine analysis with an elevated tetradecenoylcarnitine (C14:1) peak suggested a possible diagnosis of acyl-CoA dehydrogenase very long chain deficiency (ACADVLD). Whole genome sequence analysis of one affected dog and 191 controls revealed a nonsense variant in the ACADVL gene encoding acyl-CoA dehydrogenase very long chain, c.1728C>A or p.(Tyr576*). The variant showed perfect association with the phenotype in the 10 affected and more than 500 control dogs of various breeds. Pathogenic variants in the ACADVL gene have been reported in humans with similar myopathic phenotypes. We therefore considered the detected variant to be the most likely candidate causative variant for the observed exercise induced myopathy. To our knowledge, this is the first description of this disease in dogs, which we propose to name exercise induced metabolic myopathy (EIMM), and the identification of the first canine pathogenic ACADVL variant. Our findings provide a large animal model for a known human disease and will enable genetic testing to avoid the unintentional breeding of affected offspring.